COGNITIVE IMPAIRMENT AND BASIC PERSONAL AUTONOMY IN OLD AGE ADULTS - Álvarez Hernández, Joaquín; Sicilia Molina, Mercedes (Anales de Psicología / Annals of Psychology, 2007)
This study pretends to meet the mental condition of aged and what activities of the basic personal autonomy area part of its repertoire, comparing these variables, attending to sex and age. Also it has wanted to be investigated on the degree of relation between the cognitive impair-ment in the major persons and his level of autonomy in basic activities The purpose of this investigation ist to detect the most deficit areas, which could be the object in the future for psichological, social and sanitary interventions in this field.The results of this investigation provide us with a reliable knowledge, till now unknown, about the real situation of these persons, aged between 60 and 102.